Whole genome sequencing to inform the epidemiology of Plasmodium falciparum malaria in the elimination setting of Malaysia - Mark K. I., Tan; Nina, Billows; Paul C. S., Divis; Cyrus, Daneshvar; Jonathan, Edgeworth; Janet Cox, Singh; Susana, Campino; Taane G., Clark (Springer Nature, 2026)
Background Imported malaria cases, driven by human migration and travel, pose a significant challenge to malaria elimination efforts. Genomic approaches have become essential for distinguishing between local transmission and imported infections. The state of Sarawak, Malaysia, provides a pertinent example of a malaria-eliminating setting under pressure from Plasmodium parasite importation.